2011
DOI: 10.1038/onc.2011.196
|View full text |Cite
|
Sign up to set email alerts
|

Conserved features of cancer cells define their sensitivity to HAMLET-induced death; c-Myc and glycolysis

Abstract: HAMLET is the first member of a new family of tumoricidal protein-lipid complexes that kill cancer cells broadly, while sparing healthy, differentiated cells. Many and diverse tumor cell types are sensitive to the lethal effect, suggesting that HAMLET identifies and activates conserved death pathways in cancer cells. Here we investigated the molecular basis for the difference in sensitivity between cancer cells and healthy cells. Using a combination of small hairpin RNA inhibition, proteomic and metabolomic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 53 publications
4
50
0
Order By: Relevance
“…Furthermore, a reduction in the extracellular glucose levels or degree of glycolysis, predominantly the aerobic glycolysis of tumor cells known as the Warburg Effect, of A549 lung carcinoma cells resulted in an enhanced HAMLET-sensitivity [83]. HAMLET was shown to bind and reduce the activity of the glycolytic enzyme hexokinase 1 in the A549 carcinoma cells, which could partly explain the inhibitory effect of HAMLET on glycolysis [83].…”
Section: Tumor Cell Death Mechanisms Of Hamletmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a reduction in the extracellular glucose levels or degree of glycolysis, predominantly the aerobic glycolysis of tumor cells known as the Warburg Effect, of A549 lung carcinoma cells resulted in an enhanced HAMLET-sensitivity [83]. HAMLET was shown to bind and reduce the activity of the glycolytic enzyme hexokinase 1 in the A549 carcinoma cells, which could partly explain the inhibitory effect of HAMLET on glycolysis [83].…”
Section: Tumor Cell Death Mechanisms Of Hamletmentioning
confidence: 99%
“…An elevated expression level of c-Myc, an oncogene that has the ability to bind a significant fraction of all known gene promoters, has been shown to increase HAMLET-sensitivity of various tumor cells, suggesting that the level of c-Myc expression could be a direct determinant of HAMLET susceptibility [83]. Furthermore, a reduction in the extracellular glucose levels or degree of glycolysis, predominantly the aerobic glycolysis of tumor cells known as the Warburg Effect, of A549 lung carcinoma cells resulted in an enhanced HAMLET-sensitivity [83].…”
Section: Tumor Cell Death Mechanisms Of Hamletmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in patients and animal models have confirmed this selectivity and demonstrated therapeutic efficacy against several tumor types ( 16 -20). HAMLET has broad tumoricidal activity unrelated to well defined cellular responses such as apoptosis (21)(22)(23). Essential aspects of the conserved death response to HAMLET have been defined, including the dependence on oncogenic transformation (22), proteasome inhibition (24), and nucleosome-histone binding (25).…”
mentioning
confidence: 99%
“…HAMLET has broad tumoricidal activity unrelated to well defined cellular responses such as apoptosis (21)(22)(23). Essential aspects of the conserved death response to HAMLET have been defined, including the dependence on oncogenic transformation (22), proteasome inhibition (24), and nucleosome-histone binding (25). We have recently identified ion channel activation as a new, unifying mechanism of HAMLET tumoricidal effect (23).…”
mentioning
confidence: 99%